Service Quality, Customer Satisfaction, Customer Trust, and Customer Loyalty in the Service of Pediatric Polyclinic (Case Study at Private H Hospital of East Jakarta, Indonesia) - Indrawati, Ratna; Elizar, Christian; Mutiara, Rina; Roespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
Customer loyalty is considered as an important key to the success and profit of a hospital, so that a decrease in the number of visits from old patients or subscribed patients in the pediatric polyclinic of Private H Hospital is a serious problem. The purpose of this research is to determine the effect of service quality on customer loyalty with customer satisfaction and trust as an intervening variable in the services of a pediatric polyclinic in Private H Hospital. The research used SEM method on 190 respondents. The test results of the model has met the criteria of Goodness of Fit in which the t-value of service quality to customer satisfaction is 14.71, service quality to customer trust is 16.10, service quality to customer loyalty is 2.16, customer satisfaction to customer loyalty is 0.83, customer trust to customer loyalty is 3.13. Customer trust significantly mediates the effect of service quality on customer loyalty while customer satisfaction cannot serve as a mediator since about 70% of patients at the pediatric polyclinic of Private H Hospital are JKN members. By maintaining customer trust through the provision of services based on hospital accreditation standards and continuous evaluation, customer loyalty will increase as marked by the re-visit of patients even though there are other pediatric polyclinics offering more, even customers will recommend the pediatric polyclinic of Private H Hospital to other people.